Microbiological Analysis of Some Raw Fish Samples - Das, Monika; Hafiz, Fauzia; Ahmed, M Kawser; Parveen, Sahana (Bangladesh Journal of Microbiology, 2008)
Total load of bacteria, fungi and pathogenic microorganisms in muscle-and-skin samples of 12 different species of fish were analyzed. Highest standard plate count (5.1 x 106 cfu/g) was observed in Batashi (Clupisoma atherinoides) and lowest (2.3 x 105 cfu/g) in Rui (Labeo rohita). Total bacterial load was almost similar in case of other fishes. Mold count was highest (7.5 x 102 cfu/g) in shrimp (Penaeus indicus) and lowest (8.0 x 101 cfu/g) in Pabda (Ompok pabda). Yeast count varied between 1.0 x 103 cfu/g in Batashi and 7.0 x 101 cfu/g in Rui. Total coliform and faecal coliform were detected in all the fish samples. Coliform count measured by most probable number (MPN) method was found to be 240/g in all fish samples. Faecal coliform count in the fish samples varied from 2.8 to 240/g. Salmonella was detected in at least two-third of the samples analysed. High microbial load in raw fishes indicates that raw fish would decompose very quickly at ambient temperature, and the presence of coliforms and Salmonella indicates the raw fish handling is not safe. Keywords: Fish, Microbiological analysis, Pathogens Bangladesh J Microbiol, Volume 24, Number 1, June 2007, pp 67-69